Fractal characteristics of displacement and cracks in the Baishuihe landslide in the Three Gorges Reservoir Area - Yuanhua XIE; Guowei ZHANG; Zongwei CAO; Fasheng MIAO (地质科技通报, 2024)
Objective Surface displacement and crack development are the most intuitive manifestations of landslide deformation and evolution. Therefore, revealing the characteristics and evolution stages of landslide deformation and failure through displacement monitoring and surface crack survey is highly practical. Methods In this study, the Baishuihe landslide in the Three Gorges Reservoir Area is selected as the research case, and monitoring data from 2003-2016 for this landslide are systematically collected and analyzed, taking monitoring points ZG93 and ZG118 as example. First, the fractal parameter Hurst index R/S analysis is carried out for the displacement data. Second, the multiple fractal dimensions of the displacement of the two monitoring points are calculated every year. Finally, the theory of stage matching of landslide cracks is introduced, and the crack fractal dimension of the Baishuihe landslide is determinated. Results The results show that there is a certain positive correlation between the landslide displacement sequences, and the fractal dimension H index of the two monitoring points is greater than 0.5. The evolution process of the Baishuihe landslide can be divided into a steady deformation state (from June 2003 to June 2007), an accelerated deformation state (from June 2007 to December 2009), and a steady deformation state (from December 2009 to December 2015). According to the matching law of crack stages, the development of the landslide is the initial deformation stage. Conclusion The research results have a certain guiding significance for revealing the evolutionary state of reservoir landslides.